Evaluation of two commercially-available Salmonella vaccines on Salmonella in the peripheral lymph nodes of experimentally-infected cattle. (October 2020) - Edrington, Thomas S.; Arthur, Terrance M.; Loneragan, Guy H.; Genovese, Kenneth J.; Hanson, Devin L.; Anderson, Robin C.; Nisbet, David J.
Background: Salmonella is a common inhabitant of the ruminant gastrointestinal tract, where it often resides asymptomatically and may be shed into the feces. More recently it was discovered that Salmonella may be contained within the peripheral, non-mesenteric lymph nodes, where it is impervious to in-plant pathogen control interventions and may serve as a source of Salmonella -contamination of ground beef. Over the past 10 years considerable research effort has been expended at understanding how this pathogen gets to these lymph nodes, the duration of infection, and, most importantly, screening and developing potential intervention strategies that may be employed on farm prior to the animal being presented for slaughter. Methods: Utilizing an experimental model of Salmonella inoculation of bovine peripheral lymph nodes (PLNs), two pilot vaccine experiments were conducted to evaluate two Salmonella vaccines: Salmonella Newport Bacterial Extract (Experiment I) and Endovac-Bovi ® (Experiment II) on preventing Salmonella acquisition by these nodes. In Experiment I, 4 months following the booster vaccination, 30 steers were inoculated with three Salmonella serotypes intradermally: Newport, Montevideo, and Anatum administered to the right legs, left legs, and to the caudal thorax and abdomen, respectively. Cattle were inoculated every other day over the course of five days (three total inoculation events) and 6 and 12 days following the final Salmonella inoculation, 16 and 14 head in each treatment were euthanized, respectively. In Experiment II, 12 head of Holstein steers were utilized. Seven days following the booster and weekly thereafter for 3 weeks (four total inoculation events), cattle were inoculated as above and euthanized 7 days following final inoculation. Right and left sub-iliac, popliteal and pre-scapular lymph nodes were collected in each experiment, weighed and cultured for Salmonella . Results: In Experiment I, no treatment differences were observed in Salmonella prevalence 6 days post-inoculation (necropsy 1). However, in vaccinated cattle at the second necropsy, a reduction ( p  = 0.05) in Salmonella prevalence was observed in the sub-iliac and pre-scapular lymph nodes as well as when all nodes were evaluated collectively ( p  = 0.04). In Experiment II, the vaccine reduced ( p  = 0.03) Salmonella prevalence in the right popliteal and tended ( p  = 0.09) to decrease prevalence in both popliteal lymph nodes. Conclusion: Under these experimental conditions, the data generated provide evidence of a partial vaccine effect on Salmonella within PLNs and indicate that further research may be warranted.